Exploring global economy evolution: Clusters and patterns - Sara Casagrande; Bruno Dallago (Economies, 2023)
Economic integration and globalization are expected to promote economic growth and convergence. This article offers a comparative analysis of the pace of development in terms of GDP per capita in 79 economies from 1970 to 2019. Usually, economic convergence literature aims to establish whether catching-up processes have been successful. This article verifies the existence of growth path similarities to identify clusters of countries that grow at a similar pace and react in a similar way to crises, and compares their dynamics in time. According to the results, coherently with globalization pressures, clusters have become fewer and larger. However, growth path divergences persist and suggest a cluster-based convergence. Integration processes, such as the European Union, have not influenced this trend. The extent to which these clusters are composed of structurally similar economies has been investigated and some consistencies have emerged between the composition of clusters and the classifications provided by the varieties of capitalism theory
Keywords: 330; cluster analysis; comparative economics; convergence; economic integration; economicsystem; globalization; structural change; varieties of capitalism; world economy